Center Variability in Acute Rejection and Biliary Complications After Pediatric Liver Transplantation. Issue 3 (25th August 2021) - Kanneganti, Mounika; Xu, Yuwen; Huang, Yuan‐Shung; Kitt, Eimear; Fisher, Brian T.; Abt, Peter L.; Rand, Elizabeth B.; Schaubel, Douglas E.; Bittermann, Therese
Abstract : Transplant center performance and practice variation for pediatric post–liver transplantation (LT) outcomes other than survival are understudied. This was a retrospective cohort study of pediatric LT recipients who received transplants between January 1, 2006, and May 31, 2017, using United Network for Organ Sharing (UNOS) data that were merged with the Pediatric Health Information System database. Center effects for the acute rejection rate at 1 year after LT (AR1) using UNOS coding and the biliary complication rate at 1 year after LT (BC1) using inpatient billing claims data were estimated by center‐specific rescaled odds ratios that accounted for potential differences in recipient and donor characteristics. There were 2216 pediatric LT recipients at 24 freestanding children's hospitals in the United States during the study period. The median unadjusted center rate of AR1 was 36.92% (interquartile range [IQR], 22.36%‐44.52%), whereas that of BC1 was 32.29% (IQR, 26.14%‐40.44%). Accounting for recipient case mix and donor factors, 5/24 centers performed better than expected with regard to AR1, whereas 3/24 centers performed worse than expected. There was less heterogeneity across the center effects for BC1 than for AR1. There was no relationship observed between the center effects for AR1 or BC1 and center volume. Beyond recipient and allograft factors, differences in transplant center management are an important driver of center AR1 performance, and less so of BC1 performance. Further research is needed to identify the sources of variability so as to implement the most effective solutions to broadly enhance outcomes for pediatric LT recipients.